2017
DOI: 10.4271/2017-01-0808
|View full text |Cite
|
Sign up to set email alerts
|

Injector Fouling and Its Impact on Engine Emissions and Spray Characteristics in Gasoline Direct Injection Engines

Abstract: Unlike in port fuel injection (PFI) systems, gasoline direct injection (GDI) engines deliver fuel directly into the combustion chamber. This opens up the possibility of new injection strategies and can improve efficiency and fuel consumption, especially under partial load [1,2,3]. An additional advantage is the so-called stratified charge operation, which allows adjustment of the injection and ignition timings of the engine, to further optimise engine operation [4]. In addition, the charge cooling effect obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In gasoline direct injection (GDI), tip coking can generate a progressive tip sooting that is a large source of particles. [1][2][3] High-magnification and spectrally filtered images of the injector tip showed a high probability of soot formation near the injector tip and also showed an increased probability of hard soot on the injector surface compared to inside the nozzle holes. 1,4 To our knowledge, very limited work has been published in the field of multi-hole direct injection tip wetting as a main factor of the tip coking then fouling, and no clear and detailed process has been proposed up to now.…”
Section: Introductionmentioning
confidence: 99%
“…In gasoline direct injection (GDI), tip coking can generate a progressive tip sooting that is a large source of particles. [1][2][3] High-magnification and spectrally filtered images of the injector tip showed a high probability of soot formation near the injector tip and also showed an increased probability of hard soot on the injector surface compared to inside the nozzle holes. 1,4 To our knowledge, very limited work has been published in the field of multi-hole direct injection tip wetting as a main factor of the tip coking then fouling, and no clear and detailed process has been proposed up to now.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Jiang's work found that the penetration length and mean droplet size of each jet were increased significantly, in contrast to Song's observations. An increased penetration length was also observed by Henkei et al [134]. Wang et al [69] indicated that deposits inside the counter bore could restrict air recirculation and entrainment, leading to lower exiting turbulent kinetic energy of the spray from a coked injector and producing a larger mean droplet size.…”
Section: Effect Of Injector Deposits On Engine Performancementioning
confidence: 61%
“…Results obtained by Wen et al [137] with a GDI vehicle having a mileage of 13,000 km showed that particulate mass and fuel consumption were increased by 376 and 3.02%, respectively, compared with the values obtained using fresh injectors. In addition, gaseous emissions such as THC, non-methane hydrocarbon (NMHC) and NOx increased by 17.1, 24.5 and 23.4%, respectively, and PN emissions could be increased by several orders of magnitude [133,134]. The fuel stored in the fouled injector tip deposits during injection and then released later caused diffusive combustion events and thus increased PM and PN emissions [112].…”
Section: Effect Of Injector Deposits On Engine Performancementioning
confidence: 99%
“…Investigations of the effect of injector deposits on the injector performance and thermal conditions are scarce [8,17,[80][81][82]. As a result, the mechanism of their adverse action is not completely understood.…”
Section: Effect Of the Deposits On The Injector Performancementioning
confidence: 99%